Tacrolimus-Related Cerebral Microbleeds after Lung Transplantation. (2nd December 2013) - Mechtouff, L.; Piegay, F.; Traclet, J.; Philit, F.; Boissonnat, P.; Hermier, M.; Durieu, I.; Cho, T.-H.; Nighoghossian, N.; Mornex, J.-F.
Abstract : Posterior reversible encephalopathy syndrome is a well-known complication of treatment by tacrolimus. We report 2 cases of lung transplant recipients treated with tacrolimus who developed cerebral microbleeds on T2*-weighted sequences in the acute setting of posterior reversible encephalopathy syndrome. Cerebral microbleeds may be a marker of tacrolimus-induced vasculopathy that may be detected earlier by neuropsychological and magnetic resonance imaging monitoring in transplant recipients treated with tacrolimus.